2008
DOI: 10.1097/opx.0b013e3181890dc7
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Hertel Exophthalmometry in Children, Teenagers, and Adults from Tehran, Iran

Abstract: Any eye protrusion of more than 17.8 mm for Iranian children, 19 mm for Iranian teenagers, and 19.3 mm for Iranian adults and relative eye protrusion of more than 2 mm warrants further clinical examination. Age and base value had a significant impact on normal eye protrusion values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 12 publications
6
49
2
Order By: Relevance
“…[11] attributed the higher male ocular protrusion to the greater body structure. In contrast, other researchers did not find a significant gender difference in ocular protrusion [4, 20]. In our study, there was no statistically significant difference (p=0.123) between the two genders in accordance to finding in the literature.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…[11] attributed the higher male ocular protrusion to the greater body structure. In contrast, other researchers did not find a significant gender difference in ocular protrusion [4, 20]. In our study, there was no statistically significant difference (p=0.123) between the two genders in accordance to finding in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies demonstrated a decrease in ocular protrusion values after the age of 20 years according to the involutional orbital soft tissue atrophy [16, 20, 21]. Kashkouli et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucci P et al reported Table 1 The descriptive characteristics of eye projection: number of subjects (n), mean (SD), median (min-max) for each age and gender that mean eye projection was 9.11 mm in 3-year-old, and 11.67 mm in 10-year-old children [13]. [16]. None of the children in our study had a relative exophthalmos greater than 2 mm.…”
Section: Discussionmentioning
confidence: 87%